San Francisco Department of Public Health : leading through the COVID-19 crisis - Chatman, Jennifer, (SAGE Business Cases., 2023)
Despite uncertainty about how to prevent and treat the new virus, and despite its unexpectedly rapid spread and higher death rates than the seasonal flu, San Francisco leaders stood out by emerging with effective responses for the City. One frontrunner was Jenna Bilinski, RN, MBA, COVID-19 Command Center Operations Chief and Health Services Operations Director at the San Francisco Department of Public Health (SFDPH), and Berkeley Haas EMBA, 2019. Bilinski joined the City's pandemic crisis team in February 2020, became Operations Chief, and led her team to operationalizing life-saving decisions including how the shelter-in-place (SIP) should transpire. When SFDPH made decisions such as SIP, it was Bilinski's job to determine how to put them into action. San Francisco was one of the first US cities to shut down-a decision that resulted in some of the lowest death rates among major metropolitan cities.30 How did health professionals like Bilinski lead teams, make fast and informed decisions, allocate scarce resources, and stay sane during a time of local and global crisis?